2016
DOI: 10.1039/c5mb00649j
|View full text |Cite
|
Sign up to set email alerts
|

Neurospora crassa transcriptomics reveals oxidative stress and plasma membrane homeostasis biology genes as key targets in response to chitosan

Abstract: Chitosan is a natural polymer with antimicrobial activity. Chitosan causes plasma membrane permeabilization and induction of intracellular reactive oxygen species (ROS) in Neurospora crassa. We have determined the transcriptional profile of N. crassa to chitosan and identified the main gene targets involved in the cellular response to this compound. Global network analyses showed membrane, transport and oxidoreductase activity as key nodes affected by chitosan. Activation of oxidative metabolism indicates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 64 publications
3
45
0
Order By: Relevance
“…These enzymes are mainly involved in glycolytic pathway and Kreb's cycle, generating NADH and ATP. Spot 20 was identified as short-chain dehydrogenase/ reductase which plays a important role in lipid, carbohydrate, amino acid, cofactor and xenobiotic metabolism (Kavanagh et al, 2008), and was identified to be reduced by chitosan treatment in Neurospora crassa (Lopez-Moya et al, 2016). Consistent with our results, previous transcriptomic studies revealed that chitosan treatment could disrupt the cellular energy production and reduces the expression of genes associated with lipid, carbohydrate and coenzyme metabolism in Staphylococcus aureus (Raafat et al, 2008) and S. cerevisiae (Jaime et al, 2012).…”
Section: Changes In Protein Expression Profiles In Response To Chitosansupporting
confidence: 90%
See 1 more Smart Citation
“…These enzymes are mainly involved in glycolytic pathway and Kreb's cycle, generating NADH and ATP. Spot 20 was identified as short-chain dehydrogenase/ reductase which plays a important role in lipid, carbohydrate, amino acid, cofactor and xenobiotic metabolism (Kavanagh et al, 2008), and was identified to be reduced by chitosan treatment in Neurospora crassa (Lopez-Moya et al, 2016). Consistent with our results, previous transcriptomic studies revealed that chitosan treatment could disrupt the cellular energy production and reduces the expression of genes associated with lipid, carbohydrate and coenzyme metabolism in Staphylococcus aureus (Raafat et al, 2008) and S. cerevisiae (Jaime et al, 2012).…”
Section: Changes In Protein Expression Profiles In Response To Chitosansupporting
confidence: 90%
“…Proteins related to antibiotics resistance and antioxidant defense response, including aminoglycoside phosphotransferase (spot 13), peroxiredoxin (spot 22) and ABC multidrug transporter (spot 25), increased in relative abundances after chitosan treatment. This finding is not unprecedented; for example, the expression levels of peroxiredoxin and a number of other proteins related to reactive oxygen species homeostasis in N. crassa were induced by chitosan treatment (Lopez-Moya et al, 2016). Dxidative stress was also observed in chitosan treated U. maydis (Dlicón-Hernández et al, 2017); therefore, increased expression of these proteins may be associated with an imbalance of the intracellular redox state.…”
Section: Changes In Protein Expression Profiles In Response To Chitosanmentioning
confidence: 96%
“…Moreover, the stronger hydrophobic and electrostatic interactions with the cell membrane may potentialize the stress responses of the fungus. As demonstrated for other fungi types, such as Ustilago maydis (Olicón-Hernández, Uribe-Alvarez, Uribe-Carvajal, Pardo, & Guerra-Sánchez, 2017), R. stolonifera (Alfaro-Gutiérrez, Guerra-Sánchez, Hernández-Lauzardo, & Velázquez-del Valle, 2014), Candida albicans (Pena, Sanchez, & Calahorra, 2013) and Neurospora crassa (Lopez-Moya et al, 2016), the permeabilization of the cell membrane, triggers the oxidative stress. Hence, as indicated by our study, the higher ability of our amphiphilic derivatives of binding to the cell membrane cannot be neglected and contributes to the inhibition of the fungal growth.…”
Section: Interaction Of the Amphiphilics With Model Membranesmentioning
confidence: 82%
“…The database has useful information for thoughtful functions and use of the biological system, such as from molecular-level information, especially large-scale molecular datasets generated by high-throughput and genome sequencing experimental technologies, organism and the ecosystem (http://www.genome.jp/kegg/). In present study the KC vs SC group, DEGs were significantly enriched in five pathways with Q and Pvalues < 0.05: "Biosynthesis of secondary metabolites" (591 DEGs), "Plant hormone signal transduction" (132 DEGs), "Plant-pathogen interaction" (150), Transcription factor (21) and protein export (36) were enriched. Meanwhile, in treated samples KT vs ST Biosynthesis of secondary metabolites" (483 DEGs), "Plant hormone signal transduction" (89 DEGs), "Plant-pathogen interaction" (127) and Transcription factor (8) and protein export (18) were enriched.…”
Section: Go and Kegg Enrichment Analysis Of Differential Expressed Genementioning
confidence: 56%
“…In the molecular function category (KC vs SC 8472/19544 enriched followed by KT vs KC 6663/19544), significantly enriched terms included transcription factor, transporter activity, transcription factor activity, coenzymes binding, catalytic, binding, nucleic acid binding and transducer activity. RNAseq data and GO analysis exposed plasma membrane, oxidoreductase activity, and transport as main categories induced [36]. Chitosan also enriches transport GO functions, respiration and oxidative metabolism in the model yeast Saccharomyces cerevisiae [37].…”
Section: Discussionmentioning
confidence: 98%